Pengaruh Transformasi Digital Terhadap Kinerja Pegawai Di Kantor Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sidenreng Rappang - Ikra Cahyani; Lukman Lukman; Ahmad Mannu Mannu (STISIPOL Raja Haji, 2025)
This research is motivated by the issue of inconsistency in the service time standards at the Office of Population and Civil Registration of Sidenreng Rappang Regency, indicating suboptimal employee performance, particularly in terms of service speed. Digital transformation, as an innovative solution, is expected to enhance the efficiency and effectiveness of public services. This study aims to determine the influence of digital transformation on employee performance. The research employs a quantitative approach with an associative type of study. Data collection techniques include observation, questionnaires, and literature review. The data were analyzed using validity tests, reliability tests, and simple linear regression with the help of IBM SPSS 21.0 software. The results show that digital transformation is rated as